Updated estimates of harbour porpoise (Phocoena phocoena) bycatch in the Danish North Sea bottom-set gillnet fishery - Larsen, Finn; Vinther , Morten (J. Cetacean Res. Manage., 2023)
The bycatch of harbour porpoise in the Danish North Sea bottom-set gillnet fisheries between 1987-2001 is estimated using two methods involving extrapolation of observer data. When observed entanglements are extrapolated to fleet level based on target species landings, the annual bycatch was estimated to be in the range of 2,867-7,566 harbour porpoise with a mean of 5,817. When observations are extrapolated based on fishing effort, estimates are in the range of 3,887-7,366 porpoises with a mean of 5,591. Both methods estimate a significant reduction in bycatch in the most recent years due to a decrease in both effort and landings. However, the reduction is less pronounced with the effort based method.